2012
DOI: 10.4102/ojvr.v79i1.431
|View full text |Cite
|
Sign up to set email alerts
|

Ticks infesting animals in the Sudan and southern Sudan: Past and current status

Abstract: In this review, we collate information about ticks identified in different parts of the Sudan and South Sudan since 1956 in order to identify gaps in tick prevalence and create a map of tick distribution. This will avail basic data for further research on ticks and policies for the control of tick-borne diseases. In this review, we discuss the situation in the Republic of South Sudan as well as Sudan. For this purpose we have divided Sudan into four regions, namely northern Sudan (Northern and River Nile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Jongejan et al [ 128 ] identified twenty-four adult ixodid tick species, infesting livestock and some wildlife hosts along the Blue and White Nile. More than 70 species of ticks are identified from Sudanese tick fauna, many of which are proven vector of major tick-borne diseases [ 129 , 130 , 131 ]. Three genera ( Hyalomma, Amblyomma, and Rhipicephalus ) and various species of ticks were identified from cattle, sheep, goat and camels.…”
Section: Diversity and Distribution Of Ticks In Arab Countries In mentioning
confidence: 99%
“…Jongejan et al [ 128 ] identified twenty-four adult ixodid tick species, infesting livestock and some wildlife hosts along the Blue and White Nile. More than 70 species of ticks are identified from Sudanese tick fauna, many of which are proven vector of major tick-borne diseases [ 129 , 130 , 131 ]. Three genera ( Hyalomma, Amblyomma, and Rhipicephalus ) and various species of ticks were identified from cattle, sheep, goat and camels.…”
Section: Diversity and Distribution Of Ticks In Arab Countries In mentioning
confidence: 99%
“…One of the most abundant species in Egypt (Al‐Hosary et al., ) and Sudan (Ahmed et al., , El Ghali & Hassan, ).…”
Section: Tick Vectorsmentioning
confidence: 99%
“…that infect livestock are common in central Sudan. The extraordinary climatic and ecological diversity in Sudan, ranging from the desert zone in the north to wooded savannahs in the south together with a wide range of domestic and wildlife hosts, accommodate the biological requirements of a variety of tick species (Elghali & Hassan, 2012). Amblyomma exornatum, Rhipicephalus sanguineus and nine Hyalomma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Amblyomma exornatum, Rhipicephalus sanguineus and nine Hyalomma spp. are common in northern Sudan (Hoogstraal, 1956), with H. anatolicum the most prevalent (A Elghali & Hassan, 2012). Theileria lestoquardi and T. annulata are known to be widespread across the country (Salih et al, 2003).…”
Section: Introductionmentioning
confidence: 99%